Challenges faced during antitubercular therapy - B. K. Likhitha; Shreeshail Anjutagi; Keertivardhan D. Kulkarni; Madhav Mahawar (BLDE University Journal of Health Sciences, 2024)
This case report discusses regarding a 48-year-old male with drug-sensitive tuberculosis (TB) and alcoholic liver disease, who experienced significant side effects during antitubercular therapy. The patient presented with peripheral neuropathy, deranged liver function, elevated uric acid levels, gastritis, and psychological distress during the treatment period. Modifications included the change of regimen and the symptomatic treatment of the associated side effects with regular liver function monitoring. Comprehensive patient education and counseling were provided to enhance adherence to the treatment. After the completion of therapy, the patient showed near complete resolution in chest X-ray with the remission of symptoms. This case emphasizes the importance of tailored management to address the challenges during the therapy and ensure successful TB treatment outcomes.